Automatization of calculations in the Geofarmer App to assess Farm's performance in terms of climate smartness - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The CSA farm calculator (data capture and automatic calculations of the 7 core indicators is avaible in Geofarmer. It includes 43 new variables that correspond to the calculate cost and benefit, supply and demand of calories, of fodder, of nitrogen, CO2 emissions at crop and animal level.